Respuesta :
Yes, here is how we know.
First subtract the first two terms.
4 - ( - 1 ) = 5
Then compare it when you subtract the next pair
-1 - (-6) = 5
Then the next
-6 - (-11) = 5
And lastly
-11 - (-16) = 5
First subtract the first two terms.
4 - ( - 1 ) = 5
Then compare it when you subtract the next pair
-1 - (-6) = 5
Then the next
-6 - (-11) = 5
And lastly
-11 - (-16) = 5
Yes, it is an arithmetic sequence. The common difference is -5. Each term has been discovered by subtracting 5 from the previous.